Understanding the Origin of Irreversible Capacity loss in Non-Carbonized Carbonate − based Metal Organic Framework (MOF) Sulfur hosts for Lithium − Sulfur battery. (1st March 2017) - Shanthi, Pavithra M.; Hanumantha, Prashanth J.; Gattu, Bharat; Sweeney, Matthew; Datta, Moni K.; Kumta, Prashant N.
Graphical abstract: Highlights: Sulfur was vapor infiltrated into nanoporous metal organic framework (S – MOFs). XPS analysis of S – MOFs shows binding of sulfur to MOF. Specific capacities ∼609 mAh/g with very low fade rate of 0.0014%/cycle obtained. Post cycling XPS analysis shows complete trapping of polysulfide in S – MOFs. Abstract: Li-Sulfur (Li-S) batteries are emergent next-generation energy storage devices due to their very high specific energy density (∼2567 Wh g −1 ) but are limited by polysulfide dissolution issues. In this work, chemically synthesized sulfur containing non-carbonized metal organic framework (S-MOF) cathodes show initial specific capacities of 1476 mAh g −1 stabilizing at ∼609 mAh g −1 with almost no fade for over 200 cycles. Post-cycled separators of the S – MOF cathodes display complete absence of polysulfides after cycle 1, 20 and 200, respectively. It was identified that the occurrence of carbonate species in the MOF structure resulted in the formation of C-S bonded species causing retention of polysulfide at the electrode surface ensuring long-term stability. However, this observed capacity drop during the first 10 cycles is attributed to the oxidation of some of the infiltrated sulfur by the MOF as determined by electrochemical and X-ray photoelectron spectroscopy (XPS) analyses. Nevertheless, the negligible fade rate (0.0014% cycle −1 ) and complete prevention of polysulfide dissolution renders these cathodes most promising candidates for Li-S batteries. Understanding of this transformation behavior in sulfur-containing MOF is essential to engineer chemically-bonded host-structures capable of efficient polysulfide trapping, a key pathway to establishing novel platforms for achieving high power Li – S batteries.